PARADOKS EFEKTIVITAS AUDIT INTERNAL DAN PENINGKATAN NPL: STUDI PADA BANK PEREKONOMIAN RAKYAT - Vebriani Natalia Gulo Nama Penulis; Ferry Laurensius (Bajang Institute, 2026)
Abstract: This study aims to evaluate the effectiveness of the internal audit function at PT Bank Perekonomian Rakyat Nusantara Bona Pasogit Dua Puluh. This study uses a measuresment framework from the Institute of Internal Auditors (IIA), and the method used is qualitative, with data collection through interviews and questionnaires with internal audit staff and management. The results of the study stated that the implementation of the internal audit function has been carried out very effectively, with an effectiveness rate of 94.5%, this shows a significant contribution to the company's operational control. However, there are still some challenges, such as limited human resources and communication issues that need to be fixed. Strategic recommendations include adding more human resources for audit staff, professional certification procurement activities, and increasing the use of audit technology to further support effectiveness.